Mamografía disminuye la mortalidad en cáncer de mama y el riesgo de cáncer de tiroides: Mammography reduces mortality in breast cancer and the risk of Thyroid Cancer (La U Investiga, 2020)
This is a bibliographic descriptive review article, the main objective is make aware to the population, doctors and technicians, about the utility of the mammography to reduce breast cancer, and disclosing their null relationship whit the development of thyroid cancer.It has been collected bibliographic information that has as general objectives:• Review the international medical literature to know the influence of the mammography in the reduction of the decreased mortality and the relationship of radiation exposure whit the development of thyroid cancer.• Establish the difference between conventional and digital mammography.• Define the need of thyroid cervical plumb protection.• Evidence that the mammography is a reliable screening test that brings more benefits than risks.
Keywords: Mammography; breast cancer; thyroid, mortality; thyroid; mortality; detection; radiation